Comparison between MAT flow fixed bed and batch fluidized bed reactors in the evaluation of FCC catalysts. 1. conversion and yields of the main hydrocarbon groups - Passamonti, Francisco Javier (2009)
A comparison was performed between the performances of a MAT-type reactor (flow fixed bed) and a CREC Riser Simulator reactor (batch fluidized bed) in the conversion of two VGO feedstocks (aromatic and paraffinic types) over three commercial equilibrium FCC catalysts under similar conditions. In both units the reaction temperatures were 500 and 550 °C. The catalyst to oil relationships were from 2.3 to 6.2 (cumulative) and 6.2, and the times were from 15 to 40 s (time on stream) and from 5 to 30 s (reaction time) in the MAT reactor and the CREC Riser Simulator reactor, respectively. A comparison of the product yield structure in each unit at the same conversion showed that they were very different due to the significant differences in the contact between reactants and catalyst and operative modes. Results were compared in terms of VGO conversion and the yields of the most important hydrocarbon groups LPG, gasoline, and coke. Some advantages were observed with data from the CREC Riser Simulator reactor, derived from the fact that yields are in general closer to commercial values, mainly concerning gasoline and coke. The yields of the main hydrocarbon groups also followed linear behaviors in this reactor, thus being easier to analyze, as selectivities did not depend on the conversion reached. On the contrary, yields showed a strong dependency on conversion in the MAT reactor, particularly in the case of gasoline and coke. The high coke yield in the first moments of the experiments in the MAT reactor could lead to modifications in the selectivities to certain reactions and products.